Lavaters Rezeption von Spaldings "Ueber die Nutzbarkeit des Predigtamtes" und Herders "An Prediger" in seiner Predigtreihe zur Apokalypse - Kohler, Daniela (Zwingliana, 2013)
After Joachim Spalding’s oeuvre, "Ueber die Nutzbarkeit des Predigtamtes" was published in 1722, Johann Caspar Lavater challenged Spalding’s view of the duties and benefits of the clerical minister. Above all, Lavater criticized Spalding’s focus on the moral aspects of religion, arguing that Spalding failed to concentrate on the true center – Christ and all Christian dogma. Lavater felt that Johann Gottfried Herder had furnished a better interpretation of ministerial responsibilities in "An Prediger. Funfzehn Provinzialblätter" (1774). Intrigued by Herder’s proclamation of the evangelical Christ, Lavater thought that he had found support for his own Christianity in Herder. His assumption was destroyed by Herder’s work on the Apocalypse in "Maran Atha" (1779). In accordance, Lavater in his sermons about the Book of Revelation sought to provide an example, not only of how to understand the last book of the New Testament, but also by emphasizing where a minister should focus his attention in order to function as a prophet of the evangelical Jesus.